Drover for Post Disaster Search and Rescue - Jyothish Chandran G; Jane Susan Jacob; Nejiya Khader; Tincy Merin Thomas (Journal of Electronic Design Engineering, 2019)
This paper is based on the real life experiences that we came across as volunteers of the flood that struck Kerala in the month of August 2018.We realized from the witnesses of the victims that most of them were rescued after quite a long time. There were also incidents where family members had to keep watch over the dead bodies of their loved ones, whose lives could have been rescued had the rescue team arrived earlier. Drones have been in use for search and rescue for some time now and so are rovers. But drones suffer from fast depletion of battery and difficulty to manoeuvre indoors while rovers find it difficult to overcome obstacles like boulders and debris. So, stand-alone units of drone or rovers are not that effective when it comes to a disaster situation like collapsed building in an earthquake. The proposed drover or the combined drone-rover platform equipped with camera and wireless transmission system will improve the effectiveness of search and rescue operations by the enhanced maneuverability it attains due to its ability to fly and traverse the ground.